2005
DOI: 10.1128/aem.71.8.4414-4426.2005
|View full text |Cite
|
Sign up to set email alerts
|

Shewanella oneidensis MR-1 Uses Overlapping Pathways for Iron Reduction at a Distance and by Direct Contact under Conditions Relevant for Biofilms

Abstract: We developed a new method to measure iron reduction at a distance based on depositing Fe(III) (hydr)oxide within nanoporous glass beads. In this "Fe-bead" system, Shewanella oneidensis reduces at least 86.5% of the iron in the absence of direct contact. Biofilm formation accompanies Fe-bead reduction and is observable both macro-and microscopically. Fe-bead reduction is catalyzed by live cells adapted to anaerobic conditions, and maximal reduction rates require sustained protein synthesis. The amount of reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
199
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 301 publications
(217 citation statements)
references
References 74 publications
(82 reference statements)
11
199
1
1
Order By: Relevance
“…alga BrY reduced iron oxides trapped within porous alginate beads. A more recent study by Lies et al (4) also demonstrated reduction of Fe(III) oxides precipitated within nanoporous glass beads by Shewanella oneidensis MR-1 (4). Importantly, these studies could not detect a compound to explain these observations or differentiate between a model where a redox active compound produced by Shewanella diffused into the bead and a model where Shewanella produced a molecule to chelate ferric iron to facilitate its return to the cell.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…alga BrY reduced iron oxides trapped within porous alginate beads. A more recent study by Lies et al (4) also demonstrated reduction of Fe(III) oxides precipitated within nanoporous glass beads by Shewanella oneidensis MR-1 (4). Importantly, these studies could not detect a compound to explain these observations or differentiate between a model where a redox active compound produced by Shewanella diffused into the bead and a model where Shewanella produced a molecule to chelate ferric iron to facilitate its return to the cell.…”
mentioning
confidence: 82%
“…m (1)(2)(3), yet bacteria such as Shewanella demonstrate an ability to transfer electrons to metals located Ͼ50 m from cell surfaces (4,5). For example, in experiments by Nevin and Lovley (5), Shewanella.…”
mentioning
confidence: 99%
“…The outer membrane cytochrome (C-type) is involved in the direct transfer of electrons produced from NADH [14]. Electron transfer through mediators: Few genera of bacteria such as Shewanella and Pseudomonas secrete some chemical species such as flavins called shuttle molecules to transfer electrons from the outer membrane of bacteria to electrodes [15,16].…”
Section: Electron Transfer Mechanismmentioning
confidence: 99%
“…(ii) indirect electron transfer mediated by flavin electron shuttles, or (iii) intercytochrome electron transfer, possibly along "nanowires" (8)(9)(10)(11)(12)(13)(14)(15)(16). Here we present the X-ray crystal structure of a decaheme terminus of an OM conduit, MtrF, and propose models from this structure into how these different types of extracellular electron transfer might occur.…”
mentioning
confidence: 99%